Implementasi Fathul Qorib dalam Maharah Al-Qira’ah dengan Menggunakan Metode Diskusi Mahasiswa Semester III Jurusan Bahasa dan Sastra Arab UIN Maliki Malang - Sri Afrida Yanti; Taufiqur Rochman; Abdul Basid (Ideas Publishing, 2023)
Fathul qorib which is part of the yellow book is a reference for knowledge in various school instutions, both madrasas and universities, including in the application of Arabic. To understand and study fathul qorib can apply maharah qiraah or reading skills with the discussion method. The research method that reseaerchers use is descriptive qualitative. The results of the research that the researcher found that students in the third semester of BK majoring in Arabic language and literature, Maulana State Islamic University Malik Ibrahim Malang by applying Fathul Qorib in maharah qira'ah and using the discussion method were able to read Arabic. This is seen from the enthusiasm and enthusiasm of students' learning while in class and the student response at the end of learning to the use of Fathul Qorib can help reading. So among the students asked that this research continue.